PENGARUH BIAYA OPERASIONAL DAN VOLUME PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Irfan Aulia Zamsy; Mariaty Ibrahim (Bisnis-Net, 2023)
This study aims to determine the effect of operating costs and sales volume on net profit in Retail Sector Companies and Food and Beverage Distributors on the Indonesia Stock Exchange. The method in research is quantitative. The type of data used is secondary data because it is obtained from documents, information, and annual income statement data of retail sector companies and food and beverage distributors on the Indonesia Stock Exchange for the period 2017 to 2022. From data analysis which includes classical assumption tests, linear regression analysis, hypothesis tests and determination coefficient tests, it is concluded that operating costs have a negative and significant effect on net income, sales volume has a positive and significant effect on net income, and the results of the F test of operating costs and sales volume on net profit show operating costs and sales volume simultaneously have a significant effect on net profit.Keywords: Operating Expenses, Sales Volume and Net Profit.